Identifikasi Potensi Pengembangan Kerbau Lokal dengan Metode Location Quotient (LQ) di Kecamatan Moa Kabupaten Maluku Barat Daya - Alam, A; Kewilaa, A I; Sairudy, A (Politeknik Negeri Lampung, 2026)
The purpose of this study was to determine the sub-districts in Southwest Maluku Regency that have the potential for developing local buffalo livestock. The method used in this study was secondary data observation of Southwest Maluku Regency which was then analyzed using Location Quotient (LQ) analysis. The results of the analysis showed that Moa District had an LQ value of 2.73. West Wetar and East Wetar Districts as well as the Romang Islands also showed high LQ values of 2.74; 2.33; and 1.16, respectively. Meanwhile, there were other sub-districts with LQ values <1, meaning they were included in the non-basic category, namely Letii, Lakor, Wetar, North Kisar, and the Southern Islands Districts. Furthermore, several sub-districts in Southwest Maluku Regency, including North Wetar, Damer, Mdona Hyera, Babar Island, Wetang Island, East Babar, Masela Island, and Dawelor Dawera, even have an LQ value of 0, indicating a very low or unrecorded buffalo population. Moa District has a clear comparative advantage in buffalo farming compared to other sub-districts in Southwest Maluku Regency. Based on livestock population data analysis, this region has the highest recorded number of buffalo, 11,610 out of a total of 13,443 buffalo in the entire regency, or approximately 86.36% of the total buffalo population in the region. Moa District demonstrates outstanding potential as a center for local buffalo development in Southwest Maluku Regency. This potential also strengthens the role of the Moa buffalo as a superior Maluku germplasm that needs to be preserved and developed sustainably